Pemahaman Hukum Taurat Menurut Teologi Anugerah Dan Implikasinya Terhadap Persepsi Antinomian - David Martinus Gulo (Institut Agama Kristen negeri Kupang, 2021)
Understanding the law in new testament concept has a diverse interpretation, especially its relation with doctrine of soteriology in church. It should be known due to differences in understanding the essence of the law itself and its position and relation to God’s grace. Also when some views see that the Grace of God in the new testament abolish the Law, then the question is will Christianity live a lawless life (antinominanism). This writing discussing the viewa of Grace theology view and comparison with the mainstream theology that was accepted in pentecostalism-charismatic branch.